Meta-Analisis Praktikalitas Penggunaan E-modul Oleh Guru Dan Peserta Didik Dalam Pembelajaran - Zulyusri; Noveridha Utama (Universitas Nusantara PGRI Kediri, 2022)
The development of science and technology requires teachers to use information technology-based learning media in the learning process. One of the efforts made by teachers is the use of electronic modules (e-modules). The e-module is an innovation from the print module that can be accessed via smartphone or personal computer (PC). E-modules can display images, videos, audio, and animations, so that the learning process become interactive. This study aims to analyze the practicality of using e-modules for teachers and students. Practicality is the ease of use of the product being develop. Meta-analysis is done by collecting similar articles by searching for articales from several journals via the internet. The sample used in this study was 10 articles related to the use of e-modules. The result of the study found that the average practicality level of using e-modules. The result of the study found that the average practicallity level of using e-modules by teachers was 0,893 in the very practical category, while the average practicality level by students was 0,879 in the very practical category. Based on the result of the analysis of the use of the developed e-module, it can be categorized as practical so that it is suitable for use in the learning process.